Agricultural expansion affects soil quality indicators in the MATOPIBA region: Brazil\'s new agricultural frontier - Locatelli, Jorge Luiz (2021)
The global increase in demand for primary resources has caused the intensification and expansion of agriculture. In Brazil, this has occurred in the MATOPIBA region (northeast region), considered the new agricultural frontier in the country. However, due to local soil and climate conditions and the effects promoted by land-use change (LUC), the sustainability of agricultural development in the region has been questioned. The tested hypothesis in this study was that agricultural expansion in the region leads to soil degradation. Therefore, a field study was conducted in a representative area of the MATOPIBA region, where the LUC effects in the soil organic matter (SOM) dynamics and the main soil physical quality indicators were evaluated. The sampling process was carried out in three uses: native vegetation - Cerrado (NV), pasture (PA) and cropland (CA). Soils were classified as Typic Haplustox (Soil Taxonomy) and as Latossolo Amarelo distrófico in the PA area, and Latossolo Vermelho Amarelo distrófico in NV and CL areas (Sistema Brasileiro de Classificação de Solos). Disturbed and undisturbed samples were collected up to 1 m, and attributes related to SOM were assessed, such as total carbon (C) and nitrogen (N) content, C of the fractions obtained through the physical fractionation of SOM, and the carbon management index (CMI). Physical attributes were obtained up to 30 cm, being indicators of soil compaction, pore distribution, air and water fluxes, and aggregate stability. The results showed that the conversion from NV to extensive PA reduced the total C and N stocks, the C content from the mineral-associated organic matter (MAOM) and of particulate organic matter (POM) fractions, and the CMI. Besides, the conversion to PA resulted in soil compaction, which consequently reduced porous space and air and water fluxes, reaching the critical levels for plant growth. On the other hand, the conversion from NV to CL did not affect the total C and N stocks. There was a decrease in the C stocks from the MAOM fraction, but the increase in C in POM was able to offset such losses. The increase observed in C levels in POM improved the CMI, indicating an increase in the SOM quality. Despite the positive effects in the SOM dynamics, the conversion from NV to CL did not promote the same impact on the assessed physical indicators. Although the critical levels for plant growth have not been reached, the establishment of CL favored soil compaction, reduced porous space, saturated hydraulic conductivity of the soil, and aggregate stability (compared to NV), which increases soil\'s susceptibility to erosion. Overall, the results obtained indicate the urgent need to adopt conservationist practices for the management of areas in the MATOPIBA region. Soil quality in PA areas can be improved by adopting optimized grazing techniques (e.g., stocking rate control and rotational grazing) and improving soil fertility (especially N). Likewise, crop rotation and machine traffic control can be viable options for improving the management of CL areas, mitigating the negative effects induced by the LUC, and supporting the provision of ecosystem services in the region.